Recurrence rates of periocular basal cell carcinoma following Mohs micrographic surgery: a retrospective study. (6th May 2016) - Sin, Chun W.; Barua, Ankur; Cook, Anne
Abstract: Background: The incidence of basal cell carcinoma (BCC) has increased during the previous decade. Mohs micrographic surgery (MMS) is the gold standard technique for BCCs. The aim of this study was to investigate the recurrence rate of periocular BCCs following MMS in a regional Mohs treatment facility in the United Kingdom. Materials and methods: The study comprised a retrospective case note review of 480 patients who underwent MMS from 2001 to 2006 for periocular BCC. Patients were identified via hospital coding databases. Medical records were reviewed, and the parameters collected include age, gender, previous BCCs and treatment modality, postoperative complications and subsequent management, site, size of lesion, histological subtype, and recurrence following MMS. Results: Three hundred and ninety of the 480 patients identified were included. The remaining patients had died before the 5‐year analysis (65), were lost to follow‐up (20), or were identified as having Gorlin's syndrome (5). The majority of BCCs were 6–10 mm (42%) and nodular (45%). Six recurrences were identified (1.5%), including one (0.3%) primary BCC and five (6.5%) recurrent BCCs at the time of the MMS. The mean follow‐up was 30 months (range 1–120 months). Conclusion: For BCC in the periocular region, MMS should be the treatment of choice for both primary and recurrent periocular BCCs. The increased recurrence rate, demonstrated by recurrent BCCs, highlights the need for a comprehensive follow‐up.